Record of hospitalizations for ambulatory care sensitive conditions: validation of the hospital information system - Tania Cristina Morais Santa Barbara Rehem; Maria Regina Fernandes de Oliveira; Suely Itsuko Ciosak; Emiko Yoshikawa Egry (Universidade de São Paulo, 2013)
OBJECTIVE: to estimate the sensitivity, specificity and positive and negative predictive values of the Unified Health System's Hospital Information System for the appropriate recording of hospitalizations for ambulatory care-sensitive conditions. METHOD: the hospital information system records for conditions which are sensitive to ambulatory care, and for those which are not, were considered for analysis, taking the medical records as the gold standard. Through simple random sampling, a sample of 816 medical records was defined and selected by means of a list of random numbers using the Statistical Package for Social Sciences. RESULT: the sensitivity was 81.89%, specificity was 95.19%, the positive predictive value was 77.61% and the negative predictive value was 96.27%. In the study setting, the Hospital Information System (SIH) was more specific than sensitive, with nearly 20% of care sensitive conditions not detected. CONCLUSION: there are no validation studies in Brazil of the Hospital Information System records for the hospitalizations which are sensitive to primary health care. These results are relevant when one considers that this system is one of the bases for assessment of the effectiveness of primary health care.